2018
DOI: 10.1115/1.4038200
|View full text |Cite
|
Sign up to set email alerts
|

A Nonlinear Viscoelastic Model for Adipose Tissue Representing Tissue Response at a Wide Range of Strain Rates and High Strain Levels

Abstract: Finite element human body models (FEHBMs) are nowadays commonly used to simulate pre- and in-crash occupant response in order to develop advanced safety systems. In this study, a biofidelic model for adipose tissue is developed for this application. It is a nonlinear viscoelastic model based on the Reese et al.'s formulation. The model is formulated in a large strain framework and applied for finite element (FE) simulation of two types of experiments: rheological experiments and ramped-displacement experiments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…The material properties of adipose tissue are among parameters to be investigated in the lap belt‐to‐pelvis interaction. The previously developed material model 23 was used for adipose tissue and briefly introduced in this section. The rheological model is based on the generalised Maxwell viscoelastic model which consists of one elastic chain for equilibrium response (EQ) in parallel with N chains of Maxwell type (NEQ) for non‐equilibrium behaviour.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The material properties of adipose tissue are among parameters to be investigated in the lap belt‐to‐pelvis interaction. The previously developed material model 23 was used for adipose tissue and briefly introduced in this section. The rheological model is based on the generalised Maxwell viscoelastic model which consists of one elastic chain for equilibrium response (EQ) in parallel with N chains of Maxwell type (NEQ) for non‐equilibrium behaviour.…”
Section: Methodsmentioning
confidence: 99%
“…However, according to a previous study, 20 κ and A were the most important parameters which have been selected for this study. Therefore, for brevity, the details of the evolution of viscous strain have been omitted here, readers are referred to References 20,23 for further information.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite these extensive studies on adipose tissue mechanics, some physical effects and the corresponding material characteristics still require further investigations. Proposing a computational model, Naseri et al identified a lack of experimental data in a testing regime combining large deformation and high testing velocities [ 44 ]. Comley and Fleck examined the uniaxial compressive behaviour of subcutaneous adipose tissue for different strain rates between 0.002 and 5700 s −1 and Grigoriadis investigated the material response of the heel fat pad for different strain rates up to 150 s −1 using a drop rig [ 27 , 33 ].…”
Section: Introductionmentioning
confidence: 99%